2003
DOI: 10.1007/s10038-003-0064-9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetics of autism spectrum disorders

Abstract: Autistic disorder belongs to a broad spectrum of pervasive developmental disorders. Autism is a clinically and genetically heterogeneous condition. It is characterized by impairment in a broad range of social interactions, communication, and repetitive patterns of behavior and interest. Although the exact etiology of the condition is not known, family and twin studies strongly support genetic factors in autism. Genome-wide scans suggest several susceptibility loci that may contain one or more predisposing gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 120 publications
0
17
0
1
Order By: Relevance
“…But they have not come to be conclusive yet [Risch et al, 1999;Jamain et al, 2003;Shastry, 2003;Vincent et al, 2004]. From a number of studies, it appears that specific genetic diseases such as cytogenetic abnormalities and single gene defects (e.g., tuberous sclerosis complex, neurofibromatosis, hypomelanosis of Ito, Williams syndrome, Moebius syndrome, Sotos syndrome, Goldenhar syndrome, CHARGE syndrome, phenylketonuria, metabolic purine disorders, etc.)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But they have not come to be conclusive yet [Risch et al, 1999;Jamain et al, 2003;Shastry, 2003;Vincent et al, 2004]. From a number of studies, it appears that specific genetic diseases such as cytogenetic abnormalities and single gene defects (e.g., tuberous sclerosis complex, neurofibromatosis, hypomelanosis of Ito, Williams syndrome, Moebius syndrome, Sotos syndrome, Goldenhar syndrome, CHARGE syndrome, phenylketonuria, metabolic purine disorders, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there has been a change in the appreciation of autism from a qualitative to a quantitative disorder, so that it is important to evaluate autistic symptoms quantitatively. Furthermore, recent studies have strongly suggested that autistic traits are continuously distributed in the general population [Constantino and Todd, 2000, 2003Ronald et al, 2005Ronald et al, , 2006b. A quantitative approach with a continuum scale thus complements categorical diagnosis [Baron-Cohen et al, 2006].…”
Section: Introductionmentioning
confidence: 99%
“…Our random sample of cases included males only, and the ascertainment method may thus be biased. The lack of female cases could be due to different clinical presentation 56 or that autism is under-recognized in Faroese females for cultural reasons, or due to early environmental influences. 57 Alternatively, the malefemale ratio could be a chance finding owing to the limited number of cases included.…”
Section: Discussionmentioning
confidence: 99%
“…Autism is a neurodevelopmental disorder with a strong genetic basis [Wassink and Piven, 2000;Folstein and Rosen-Sheidley, 2001;Cook, 2001;Andres, 2002;Shastry, 2003;Yonan et al, 2003;Jamain et al, 2003a,b;Muhle et al, 2004;Wassink, 2004]. The diagnostic criteria for autism spectrum disorders, including Asperger syndrome, continue to be refined, a difficult task given the complexity of the syndrome and the variability in symptoms and severity.…”
Section: How Would You Model Autism In Mice?mentioning
confidence: 99%